Hubungan Tingkat Pengetahuan Ibu Hamil Tentang COVID-19 Dengan Tingkat Kecemasan Selama Kehamilan Masa Pandemi Pada Puskesmas di Kota Kupang - Sidauruk, Debora Maryke Idawati; Koamesah, Sangguana Marthen Jacobus; Nurina, Rr. Listyawati; Ratu, Kristian (Universitas Nusa Cendana, 2023)
ABSTRACTBackground : Coronavirus Disease 2019 (COVID-19) is an infection of the SARS- CoV-2 virus in the respiratory tract that has spread to various regions of the country and has been declared a global pandemic. The COVID-19 virus can infect anyone, including pregnant women as a special group that is susceptible to infection with the virus. During pregnancy, the pregnant woman experiences many physiological and psychological changes that bring discomfort and cause anxiety. Before the pandemic, pregnant women experienced anxiety related to preparation for childbirth, lack of family support, etc. During the COVID-19 pandemic, pregnant women anxiety have increased because they are faced with a lot of concerns related to the health of the pregnant woman herself, the fetus, and her family. In addition, too many information from various media about COVID-19 and pregnant women's lack of knowledge about transformations during pregnancy are also causes anxiety for pregnant women. Knowledge owned by pregnant women about pregnancy during the COVID-19 pandemic can be a future reference for how pregnant women behave in facing and overcoming anxiety related to COVID-19 Objective : This study aims to determine the correlation between pregnant women’s level of knowledge about COVID-19 and the level of anxiety in pregnancy during a pandemic at the Community Health Center in Kupang City.Method : This study used an analytic observational research design with a cross- sectional design. Sampling using probability sampling technique, which is stratified random sampling with total sample about 105 people. Data was accumulated by using Pregnant Women's Knowledge about COVID-19 Questionnair and the Hamilton Anxiety Rating Scale questionnaire that had given to pregnant women at the health center in Kupang City. The data were analyzed by using Spearman Rank test.Result : The results after using the Spearman rank test, there is a significant corrrelation between the pregnant women’s level of knowledge about COVID-19 and pregnancy level of anxiety during pandemic at health centers in Kupang City with p value= 0.007. Conclusion : There is a significant correlation between the pregnant women’s level of knowledge about COVID-19 and pregnancy level of anxiety during pandemic at health centers in Kupang City.Keywords : Level of knowledge, level of anxiety